2007
DOI: 10.1051/0004-6361:20066821
|View full text |Cite
|
Sign up to set email alerts
|

Multi-wavelength study of the gravitational lens system RXS J1131-1231

Abstract: Aims. We discuss and characterize micro-lensing among the 3 brightest lensed images (A-B-C) of the gravitational lens system RXS J1131-1231 (a quadruply imaged AGN) by means of long slit optical and NIR spectroscopy. Qualitative constraints on the size of different emission regions are derived. We also perform a spectroscopic study of two field galaxies located within 1.6 arcmin radius from the lens. Methods. We decompose the spectra into their individual emission components using a multi-component fitting app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(121 citation statements)
references
References 44 publications
6
114
1
Order By: Relevance
“…(7)). This is equivalent to adopt a value of μ c as close as possible to 1, thus ensuring that the macro-and microamplifications are best separated (see also Sluse et al 2007). Unless M A, this method provides a reasonably accurate estimate of M, and then of μ c .…”
Section: Discussionmentioning
confidence: 99%
“…(7)). This is equivalent to adopt a value of μ c as close as possible to 1, thus ensuring that the macro-and microamplifications are best separated (see also Sluse et al 2007). Unless M A, this method provides a reasonably accurate estimate of M, and then of μ c .…”
Section: Discussionmentioning
confidence: 99%
“…In order to provide a more global overview of the variety of signals which may be observed, we completed our main sample with five systems we studied elsewhere: SDSS J0924+0219 (Eigenbrod et al 2006a), H1413+117 (Hutsemékers et al 2010), J1131-1231 (Sluse et al 2007), HE 2149-2745 (Burud et al 2002), and Q2237+0305 (Eigenbrod et al 2008;Sluse et al 2011). This is not a complete list of known microlensed quasars (see e.g.…”
Section: The Extended Samplementioning
confidence: 99%
“…Pooley et al 2007;Floyd et al 2009;Hutsemékers et al 2010;Dai et al 2010;Blackburne et al 2011;Muñoz et al 2011). Studies of BLR microlensing are more sparse and detections have been reported only for a handful of systems (Richards et al 2004;Wayth et al 2005; Keeton et al 2006;Sluse et al 2007;Hutsemékers et al 2010). In this paper, we present a careful re-extraction and analysis of archive spectra of a sample of 13 lensed quasars initially observed with the aim of measuring the redshift of the lensing galaxy.…”
Section: Introductionmentioning
confidence: 99%
“…We then used additional observations of the standard star GD140 to calibrate the flux scale, and thus, derived wavelength-and flux-calibrated spectra. There are several approaches to extract individual spectra of quasar images and galaxies in lens systems on a long slit (e.g., Fassnacht & Cohen 1998;Ofek et al 2006;Sluse et al 2007). In particular, Sluse et al (2007) extracted spectra of three close quasar images along a slit by fitting three 1D PSF profiles in the spatial direction for each wavelength bin.…”
Section: Gtc Optical Spectroscopymentioning
confidence: 99%
“…There are several approaches to extract individual spectra of quasar images and galaxies in lens systems on a long slit (e.g., Fassnacht & Cohen 1998;Ofek et al 2006;Sluse et al 2007). In particular, Sluse et al (2007) extracted spectra of three close quasar images along a slit by fitting three 1D PSF profiles in the spatial direction for each wavelength bin. Our extraction method relies on the scheme of Sluse et al, but it incorporates some procedures to accurately account for off-axis quasar images and galaxies.…”
Section: Gtc Optical Spectroscopymentioning
confidence: 99%